2017
DOI: 10.1016/j.meatsci.2017.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Genomic prediction for beef fatty acid profile in Nellore cattle

Abstract: The objective of this study was to compare SNP-BLUP, BayesCπ, BayesC and Bayesian Lasso methodologies to predict the direct genomic value for saturated, monounsaturated, and polyunsaturated fatty acid profile, omega 3 and 6 in the Longissimus thoracis muscle of Nellore cattle finished in feedlot. A total of 963 Nellore bulls with phenotype for fatty acid profiles, were genotyped using the Illumina BovineHD BeadChip (Illumina, San Diego, CA) with 777,962 SNP. The predictive ability was evaluated using cross val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 49 publications
3
18
0
Order By: Relevance
“…Other studies in sheep underlined the higher accuracy of genomic methods compared with the pedigree-based approach for milk and meat production traits (Daetwyler et al, 2012;Legarra et al, 2014;Baloche et al, 2014). Moreover, GS studies carried out in beef cattle on muscle FA composition reported for some of FA also investigated in this study a similar pattern of GEBV accuracy (Chen et al, 2015;Chiaia et al, 2017;Zhu et al, 2017).…”
Section: Accuracy Of Ebv and Gebv Predictionssupporting
confidence: 72%
“…Other studies in sheep underlined the higher accuracy of genomic methods compared with the pedigree-based approach for milk and meat production traits (Daetwyler et al, 2012;Legarra et al, 2014;Baloche et al, 2014). Moreover, GS studies carried out in beef cattle on muscle FA composition reported for some of FA also investigated in this study a similar pattern of GEBV accuracy (Chen et al, 2015;Chiaia et al, 2017;Zhu et al, 2017).…”
Section: Accuracy Of Ebv and Gebv Predictionssupporting
confidence: 72%
“…Accordingly, higher levels of concentrate feed in the finishing period of the animals confined result in a higher concentration of oleic acid and MUFA in the intramuscular fat [31]. Although the adipogenic mechanism is extremely complex, several genes were identified and confirmed as being responsible for fatty acid composition in beef [20,[32][33][34][35][36][37][38][39][40][41].…”
Section: Literature Review 21 Fat Depositionmentioning
confidence: 99%
“…However, the high cost to obtain the phenotypic information and the fact that this trait can be only obtained after slaughter limits the genetic improvement through traditional selection. Although FA profile is not considered selection criteria, genomic selection is an important tool to improve the genetic progress of this trait, since the animal can be availed early in life, even at birth, reducing the generation interval and low cost [32]. In this sense, Cesar et al [37] and Aboujaoude et al [35] reported that selection for beef FA profile in Zebu cattle is very feasible, since there is additive genetic variation for most beef fatty acids in Zebu cattle.…”
Section: Genetic Factor That Influence the Fatty Acid Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Onogi et al [68] evaluated the predictive ability of genomic selection in FA composition of Japanese Black catle, using single-step genomic-best linear unbiased method. Recently, Chiaia et al [69] evaluated the genomic predictability for beef faty proile in Nelore breed and concluded that genomic information can assist in improving FA proile in Zebu animals, since the use of genomic information yielded genomic values for FA proile with accuracies ranging from low to moderate. The authors also concluded that none of the evaluated methods (SNP-BLUP, Bayesian Lasso, BayesC, and BayesCπ) excelled in terms of accuracy; however, the SNP-BLUP method allows obtaining less-biased genomic evaluations; thereby, this method is more feasible when taking account the computational cost.…”
Section: Genomic Selection and Genome-wide Association Studies For Bementioning
confidence: 99%